Extracellular matrix and morphogenesis in cnidarians: a tightly knit relationship - Bergheim, Bruno Gideon; Özbek, Suat (Essays in biochemistry, 2019)
Abstract. Cnidarians, members of an early-branching metazoan phylum, possess an extracellular matrix (ECM) between their two epithelial cell layers, called the mesoglea. The cnidarian ECM, which is best studied in Hydra, contains matrix components reflective of both interstitial matrix and basement membrane. The identification of core matrisome components in cnidarian genomes has led to the notion that the basic composition of vertebrate ECM is of highly conserved nature and can be traced back to pre-bilaterians. While in vertebrate classes ECM factors have often diverged and acquired specialized functions in the context of organ development, cnidarians with their simple body plan retained direct links between ECM and morphogenesis. Recent advances in genetic manipulation techniques have provided tools for systematically studying cnidarian ECM function in body axis patterning and regeneration.